The Republican Party and the war on poverty - McLay, Mark (New perspectives on the American presidency., 2021)
Mark Maclay examines the part the Republican Party played in shaping and eventually curtailing President Johnson's War on Poverty. He shows how Republican politicians and presidents consistently influenced how the 'war' was fought, before President Reagan symbolically ended the effort with his social welfare cuts in 1981.